Understanding Organizational Commitment Dynamics:Perspectives From Malang District Government Apparatus - Fadilah, Mega Fianita; Kirana, Prambayu Candra (Badan Perencanaan Pembangunan Kota Malang, 2024)
This study aims to investigate the dynamics of organizational commitment in the Malang District Government, focusing on the impact of organizational support on work discipline and the mediating role of organizational commitment. Employing a quantitative-explanatory approach, the research involved all Civil Servants (PNS) as the population. Data collection utilized a questionnaire distributed to 45 respondents selected through census sampling, with analysis conducted using Smart Partial Least Square (PLS)-3. Results indicate that while organizational support insignificantly affects work discipline, it significantly influences organizational commitment. Additionally, organizational commitment positively impacts employee work discipline. Notably, organizational commitment fully mediates the relationship between organizational support and employee work discipline within the National Land Agency of Malang Regency. This study emphasizes the significance of enhancing organizational support to foster organizational commitment, thereby improving employee work discipline.